Covering active material, battery using same, and method for producing covering active material

By configuring a specific carbon compound on the surface of the battery's positive active material to form a covering layer, the problem of increased battery resistance under endurance testing is solved, and the battery's long life and efficiency are improved.

CN119318033APending Publication Date: 2025-01-14PANASONIC HOLDINGS CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380044688.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-10
Filing Date
2023-05-09
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The prior art is difficult to effectively suppress the increase in battery resistance under the endurance test, which affects the long life and efficiency of the battery.

Method used

A coating layer is formed by arranging a specific carbon compound on the surface of the positive electrode active material. Specifically, it contains the compound represented by the composition formula (1) and carbon having a C1s peak with a bonding energy of 288.5±1.5 eV. The atomic ratio of carbon is XC The atomic ratio XM to other elements M satisfies a specific proportional relationship.

Benefits of technology

It effectively suppresses the increase in battery resistance caused by endurance testing and improves the long life and efficiency of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119318033A_ABST
    Figure CN119318033A_ABST
Patent Text Reader

Abstract

This covering active material (130) is provided with a positive electrode active material (110) and a covering material (111) that covers at least a part of the surface of the positive electrode active material (110). The covering material (111) contains a compound represented by compositional formula (1) and carbon belonging to a C1s peak having a bonding energy of 288.5 + / -1.5 eV. In formula (1), a, b, and c are positive real numbers, and M is at least one element other than Li and O. On the surface of the covering active material (130), the atomic ratio XC of carbon and the atomic ratio XM of M satisfy the relationship represented by formula (2). LiaMbOc (1) 0.29 < = XC / (XM + XC) (2)
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a coated active material, a battery using the same, and a method for producing the coated active material. Background Art

[0002] Patent Document 1 discloses a composite active material containing carbonaceous material.

[0003] Patent Document 2 discloses a coated positive electrode active material containing a carbonate.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: International Publication No. 2013 / 099878

[0007] Patent Document 2: International Publication No. 2015 / 050031 Summary of the invention

[0008] Problems to be solved by the invention

[0009] In the conventional technology, it is required to suppress the increase in battery resistance caused by a durability test.

[0010] Means for solving problems

[0011] The present disclosure provides a covering active material, wherein the covering active material comprises:

[0012] Positive electrode active material, and

[0013] a covering material covering at least a portion of the surface of the positive electrode active material,

[0014] The coating material includes a compound represented by the following composition formula (1) and carbon belonging to a C1s peak having a bonding energy of 288.5±1.5 eV,

[0015] In formula (1), a, b and c are positive real numbers, M is at least one element other than Li and O,

[0016] On the surface of the active material, the atomic ratio of carbon is X C The atomic ratio X with the above M M The relationship of the following formula (2) is satisfied.

[0017] Li a M b O c (1)

[0018] 0.29≤X C / (X M +X C) (2)

[0019] Effects of the Invention

[0020] According to the coated active material of the present disclosure, it is possible to suppress an increase in battery resistance caused by a durability test. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a cross-sectional view showing a schematic structure of the covering active material 130 in the first embodiment.

[0022] Figure 2 This is a cross-sectional view schematically showing the structure of a positive electrode material 1000 in the second embodiment.

[0023] Figure 3 This is a cross-sectional view schematically showing the structure of a battery 2000 in the third embodiment.

[0024] Figure 4 It means X C / (X Nb +X C ) and the relationship between the initial resistance and X C / (X Nb +X C ) and the resistance change rate.

[0025] Figure 5 This is a graph showing the element distribution map in the depth direction of the covering active material of Comparative Example 1.

[0026] Figure 6 This is a graph showing the element distribution map in the depth direction of the covering active material of Example 4.

[0027] Figure 7 This is a graph showing the C1s XPS spectra of the covering active materials of Example 6 and Comparative Example 1. DETAILED DESCRIPTION

[0028] (Knowledge that forms the basis of this disclosure)

[0029] The materials used as solid electrolytes have high ion conductivity, but on the other hand, they are chemically unstable and easily degraded by contact with other materials. Therefore, the interface design between the solid electrolyte and other materials plays an important role in reducing the resistance of the battery. For example, if a lithium composite oxide is in direct contact with a sulfide solid electrolyte, diffusion of elements occurs near the interface between the two, forming a degraded layer. The formation of the degraded layer manifests itself in the form of an increase in the resistance of the battery during charge and discharge.

[0030] As a method for preventing such degradation, it is known to form a covering layer of an ion-conducting oxide such as lithium niobate on the surface of the active material. The covering layer needs to be uniformly formed on the surface of the active material with a thickness that does not hinder ion conduction, for example, a thickness of several nanometers to hundreds of nanometers. However, since the active material is a particle of several microns in size with unevenness on the surface, the method of forming a covering layer on its surface is limited. As one method, a method of forming a covering layer by mixing an organic metal compound with an active material and calcining the mixture can be cited. As another method, a method of forming a covering layer by blowing a solution containing metal ions onto the active material while drying the active material can be cited. Either method is a liquid phase method, so the thickness of the covering layer becomes uneven, or a portion where the covering layer does not exist is generated. The covering layer can also be formed by a gas phase method such as sputtering, but the thickness of the covering layer is insufficient and it is difficult to fully obtain the protective effect of the active material.

[0031] Based on this background, the inventors have conducted in-depth research on the composition of active materials suitable for suppressing the increase in battery resistance caused by endurance tests. As a result, it was found that by configuring a specific carbon compound on the surface of the active material, the increase in battery resistance caused by the endurance test can be suppressed, thereby completing the covered active material disclosed in the present invention. It should be noted that "endurance test" refers to a test of repeated charge and discharge at a high rate in a high temperature atmosphere as described in the column of the embodiment.

[0032] (Overview of one aspect of the present disclosure)

[0033] The first embodiment of the present disclosure has a covering active material having

[0034] Positive electrode active material, and

[0035] A covering material covering at least a portion of the surface of the positive electrode active material

[0036] Covering active substances,

[0037] The coating material includes a compound represented by the following composition formula (1) and carbon belonging to a C1s peak having a bonding energy of 288.5±1.5 eV,

[0038] In formula (1), a, b and c are positive real numbers, M is at least one element other than Li and O,

[0039] On the surface of the active material, the atomic ratio of carbon is X C The atomic ratio X with the above M M The relationship of the following formula (2) is satisfied.

[0040] Li a M b Oc (1)

[0041] 0.29≤X C / (X M +X C ) (2)

[0042] According to the coated active material of the present disclosure, it is possible to suppress an increase in battery resistance caused by a durability test.

[0043] In the second aspect of the present disclosure, for example, the covered active material according to the first aspect, wherein the atomic ratio X C With the above atomic ratio X M The relationship of the following formula (3) may also be satisfied. With such a configuration, the effect of suppressing the increase in resistance is enhanced.

[0044] 0.29≤X C / (X M +X C )<0.67 (3)

[0045] In the third aspect of the present disclosure, for example, in the covering active material according to the first or second aspect, the carbon may be distributed in a region from the surface of the covering active material to a depth of 50 nm or less. If such a configuration is used, the ion conductivity of the covering material is not easily impeded.

[0046] In a fourth aspect of the present disclosure, for example, in the covered active material according to any one of the first to third aspects, the M may be at least one element selected from the group consisting of metal elements and semi-metal elements.

[0047] In the fifth aspect of the present disclosure, for example, in the covered active material according to any one of the first to fourth aspects, the above-mentioned M may be in a trivalent state, a tetravalent state, a pentavalent state, or a mixed state thereof. If such a configuration is used, the ion conductivity of the covering material can be improved, and thus the resistance of the battery can be further reduced.

[0048] In a sixth aspect of the present disclosure, for example, in the coated active material according to any one of the first to fifth aspects, M may include niobium. When the coating material includes niobium, the lithium ion conductivity of the coating material can be improved.

[0049] In the seventh aspect of the present disclosure, for example, in the covered active material according to any one of the first to sixth aspects, the M may include at least one selected from the group consisting of nitrogen, sulfur, and phosphorus. If such a structure is used, the structure of the covering material becomes easily amorphous, and the lithium ion conductivity of the covering material is improved.

[0050] In the eighth aspect of the present disclosure, for example, in the coated active material according to any one of the first to seventh aspects, the positive electrode active material may also include a lithium-containing transition metal oxide having a layered rock salt structure. By using such a material, excellent charge and discharge characteristics can be achieved.

[0051] A battery according to a ninth aspect of the present disclosure includes

[0052] A positive electrode comprising the coated active material according to any one of the first to eighth aspects.

[0053] A battery according to a tenth aspect of the present disclosure includes:

[0054] A positive electrode and a negative electrode comprising the active material covered according to any one of the first to eighth aspects, and

[0055] An electrolyte layer is disposed between the positive electrode and the negative electrode.

[0056] According to the present disclosure, it is possible to provide a battery in which an increase in resistance caused by a durability test is suppressed.

[0057] In the eleventh aspect of the present disclosure, for example, in the battery according to the tenth aspect, the electrolyte layer may contain a sulfide solid electrolyte. With such a configuration, the charge and discharge efficiency of the battery can be further improved.

[0058] The method for producing a covered active material according to the twelfth aspect of the present disclosure includes:

[0059] covering the positive electrode active material with a covering material; and

[0060] The positive electrode active material covered with the covering material is brought into contact with a processing gas containing carbon dioxide gas at a higher concentration than that of the atmosphere.

[0061] According to the production method of the present disclosure, the concentration of carbon constituting carbonate ions in the surface layer portion of the positive electrode active material covered with the covering material can be increased.

[0062] In the 13th embodiment of the present disclosure, for example, the method for manufacturing a covered active material of the 12th embodiment may further include heating the positive electrode active material covered with the covering material while contacting the processing gas. By heating, the concentration of carbon constituting carbonate ions in the surface layer of the positive electrode active material covered with the covering material can be effectively increased.

[0063] In the 14th aspect of the present disclosure, for example, according to the method for manufacturing a covered active material of the 12th or 13th aspect, the main component of the above-mentioned processing gas can also be the above-mentioned carbon dioxide gas. If carbon dioxide gas is used, the concentration of carbonate ions in the surface layer of the positive electrode active material covered with the covering material can be effectively increased.

[0064] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings. The present disclosure is not limited to the following embodiments.

[0065] (Implementation Method 1)

[0066] Figure 1 This is a cross-sectional view showing a schematic structure of the covering active material 130 in the first embodiment.

[0067] The covering active material 130 includes a positive electrode active material 110 and a covering material 111. The covering material 111 covers at least a portion of the surface of the positive electrode active material 110. The shape of the positive electrode active material 110 is, for example, a particle shape. The shape of the covering material 111 is, for example, a layer shape. The covering material 111 includes a compound represented by the following composition formula (1) and carbon belonging to the C1s peak with a bonding energy of 288.5±1.5 eV. The C1s peak is a peak that appears in the XPS (X-ray Photoelectron Spectroscopy) spectrum. The carbon belonging to the C1s peak with a bonding energy of 288.5±1.5 eV is a constituent of carbonate ions (CO3 2- ) of carbon. In formula (1), a, b, and c are positive real numbers, and M is at least one element other than Li and O. On the surface of the active material 130, the atomic ratio of carbon constituting carbonate ions is X C The atomic ratio of X to M M The relationship of the following formula (2) is satisfied.

[0068] Li a M b O c (1)

[0069] 0.29≤X C / (X M +X C ) (2)

[0070] In this specification, a layer containing carbon constituting carbonate ions may be referred to as a "carbonate layer".

[0071] On the surface of the covering active material 130, there is carbon constituting carbonate ions. In detail, carbon constituting carbonate ions is included in the covering material 111. If such a composition is utilized, even if there is a defect that cannot be eliminated by the compound of formula (1) alone or there is a thin film portion of the compound of formula (1), it is possible to prevent the contact of the positive electrode active material 110 with the solid electrolyte in the positive electrode by the carbon constituting carbonate ions. As a result, the increase in the resistance of the battery caused by the endurance test can be suppressed.

[0072] Carbon contained in organic matter, graphite, amorphous carbon, etc., causes oxidative decomposition during battery operation or causes degradation of the solid electrolyte due to the generation of electronic conductivity, and therefore does not exhibit the above-mentioned effects.

[0073] The carbon constituting the carbonate ions may also be insulating.

[0074] In addition, when the carbon constituting carbonate ions is only present between the positive electrode active material and the covering material, it is difficult to control the amount of carbon attached and the thickness of the area where the carbon is distributed. Therefore, carbon becomes a factor that hinders ion conduction, or the protective performance brought by carbon becomes insufficient. For example, it is known that lithium carbonate and / or lithium bicarbonate are present as residual alkali components on the surface of a composite oxide comprising lithium and a transition metal. However, since the amount of carbon attached and the thickness of the area where the carbon is distributed are not controlled, the protective performance brought by lithium carbonate and / or lithium bicarbonate as residual alkali components is insufficient. In addition, the compound recorded as lithium bicarbonate is amorphous, so the ratio of Li2O-H2O-CO2 takes an arbitrary value. When the ratio of H2O is large, lithium bicarbonate is likely to undergo electrochemical decomposition or thermal decomposition and deteriorate the characteristics of the battery.

[0075] Regulation X C / (X M +X C ) is set with the purpose of excluding carbon derived from carbon dioxide in the air.

[0076] Atomic Ratio X C and atomic ratio X M The relationship of the following formula (3) may also be satisfied. With such a configuration, the effect of suppressing the increase in resistance is enhanced.

[0077] 0.29≤X C / (X M +X C )<0.67 (3)

[0078] In X C / (X M +X C ) is less than 0.67, an appropriate amount of carbon is contained in the covering material 111. Since the ion conduction between the positive electrode active material 110 and the solid electrolyte in the positive electrode is not easily hindered, the increase in resistance can be more effectively suppressed. C / (X M +X C ) is within the range of 0.29 or more and less than 0.67, which can achieve both the protection performance and ion conductivity of the covering material 111.

[0079] Atomic Ratio XC and atomic ratio X M The relationship of the following formula (4) may also be satisfied. With such a configuration, the effect of suppressing the increase in resistance is further enhanced.

[0080] 0.29≤X C / (X M +X C )≤0.60 (4)

[0081] Atomic Ratio X C and atomic ratio X M The relationship of the following formula (5) may also be satisfied. With such a configuration, the effect of suppressing the increase in resistance is further enhanced.

[0082] 0.29≤X C / (X M +X C )≤0.58 (5)

[0083] Atomic Ratio X C It refers to the atomic ratio of carbon constituting carbonate ions to all elements covering the surface of the active material 130 (unit: atomic %). M It refers to the atomic ratio (unit: atomic %) of the element M to all elements covering the surface of the active material 130. The term "surface" does not necessarily refer to the outermost surface, but refers to a region with a thickness of several nanometers corresponding to the escape depth of photoelectrons in XPS measurement.

[0084] The atomic ratio X of carbon constituting carbonate ions in the surface covering the active material 130 C and the atomic ratio of M is X M This can be determined using X-ray photoelectron spectroscopy (XPS).

[0085] Atomic ratio of carbon X C It can be calculated from the peak attributed to C1s. The peak attributed to C1s appears in the XPS spectrum within the range of bonding energy of 282eV to 291eV. In the range of bonding energy of 282eV to 291eV, the peak present near 288.5±1.5eV is a peak attributed to carbon with a bond derived from carbonate ions. The peak present near 285eV is a peak attributed to carbon with other bonds. Therefore, first, the atomic ratio X of all carbon is calculated based on the peaks appearing in the range of bonding energy of 282eV to 291eV. Ctot Next, the peak of the C1s peak is fitted using a pseudo-Voigt function to separate the peaks attributable to the carbon constituting carbonate ions from the peaks attributable to other carbons. The ratio of the area of ​​the peak attributable to the carbon constituting carbonate ions to the total area of ​​the C1s peak is expressed as r. C1When expressed as C You can use X C =X Ctot × C1 To find out the formula.

[0086] Atomic ratio of M M The element contained in the cover material 111, such as a metal or semi-metal element, can be measured within a typical bonding energy range. For example, the peak attributed to Nb3d exists in the bonding energy range of 200eV to 212eV in the XPS spectrum. The Nb3d peak can be used to calculate the atomic ratio X of Nb. Nb .

[0087] The influence of charging in XPS measurement can also be corrected by assigning the peak on the lowest bonding energy side of C1s to 285 eV.

[0088] The carbon constituting carbonate ions may also be distributed in the region from the surface of the covering active material 130 to a depth of less than 50 nm. In other words, the thickness of the layer of carbon constituting carbonate ions, i.e., the carbonate layer, may also be less than 50 nm from the surface of the covering active material 130 toward the inside. The thickness of the carbonate layer is suppressed to less than 50 nm, and the ion conductivity of the covering material 111 is not easily hindered. This helps to suppress the reduction of the resistance of the battery and the increase of the resistance caused by the endurance test. By repeatedly measuring with argon etching and XPS, a distribution diagram of carbon in the depth direction can be obtained. The thickness of the carbonate layer can be calculated as the SiO2 conversion thickness using the etching conditions obtained by argon etching of a SiO2 film with a known thickness.

[0089] In the XPS spectrum, the peak at around 285 eV is a peak derived from carbon having a C-C bond. Such carbon is derived from carbon in the oil of the vacuum pump used in the XPS measurement, or from carbon tape used to fix the sample. The peak at around 288.5 eV is a peak of carbon having an O-C=O bond, that is, carbon constituting carbonate ions.

[0090] The compound contained in the coating material 111, namely Li a M b O c M in may be at least one element selected from the group consisting of metal elements and semi-metal elements. With such a configuration, the lithium ion conductivity of the covering material 111 can be improved, and the resistance of the battery can be reduced.

[0091] The compound contained in the coating material 111, namely Li a M b O cThe M in may be in a trivalent state, a tetravalent state, a pentavalent state, or a mixed state thereof. If such a configuration is used, the ion conductivity of the covering material 111 can be improved, so that the resistance of the battery can be further reduced.

[0092] When M is a polyvalent ion with a valence of 3 or more, the oxide ions contained in the covering material 111 are more strongly bonded to the polyvalent ions M, so that the bonding between lithium ions and oxide ions can be weakened. As a result, the lithium ion conductivity of the covering material 111 can be improved.

[0093] Examples of the compound contained in the covering material 111, i.e., the compound represented by formula (1), include Li-Nb-O compounds such as LiNbO3, Li-BO compounds such as LiBO2 and Li3BO3, Li-Al-O compounds such as LiAlO2, Li-Si-O compounds such as Li4SiO4, Li2SO4, Li4Ti5O 12 Li-Ti-O compounds such as Li2ZrO3, Li-Zr-O compounds such as Li2MoO3, Li-VO compounds such as LiV2O5, Li-WO compounds such as Li2WO4, Li-PO compounds such as Li3PO4, Li-NO compounds such as LiNO3, and Li-SO compounds such as Li2SO3. One selected from these compounds may be used alone, or two or more may be used in combination.

[0094] M in the compound represented by formula (1) may include niobium. That is, the covering material 111 may include a composite oxide of lithium and niobium. When the covering material 111 includes niobium, the lithium ion conductivity of the covering material 111 can be improved, and the resistance of the battery can be reduced.

[0095] M in the compound represented by formula (1) may also include at least one selected from the group consisting of nitrogen, sulfur and phosphorus. That is, the compound represented by formula (1) may also include at least one selected from the group consisting of Li-PO compounds such as Li3PO4, Li-NO compounds such as LiNO3 and Li-SO compounds such as Li2SO3. Since the covering material 111 includes at least one selected from the group consisting of nitrogen, sulfur and phosphorus, the structure of the covering material 111 becomes easy to be amorphous, and the lithium ion conductivity of the covering material 111 is improved. As a result, the resistance of the battery can be reduced.

[0096] The thickness of the layer containing the covering material 111 can also be greater than 0.1nm and less than 100nm. When the layer containing the covering material 111 has a thickness of more than 0.1nm, in the positive electrode of the battery, the direct contact between the positive electrode active material 110 and the solid electrolyte can be fully suppressed, and the side reaction of the solid electrolyte can be suppressed. As a result, the charge and discharge efficiency of the battery is improved. When the layer containing the covering material 111 has a thickness of less than 100nm, the layer containing the covering material 111 is not too thick, and the internal resistance of the battery can be fully reduced. As a result, the energy density of the battery can be improved.

[0097] The thickness of the layer containing the covering material 111 may also be greater than 1 nm and less than 40 nm. If the layer containing the covering material 111 has a thickness of more than 1 nm, the direct contact between the positive electrode active material 110 and the solid electrolyte can be more fully suppressed, and the side reaction of the solid electrolyte can be suppressed. As a result, the charge and discharge efficiency of the battery is improved. If the layer containing the covering material 111 has a thickness of less than 40 nm, the internal resistance of the battery can be more fully reduced. As a result, the energy density of the battery can be increased.

[0098] The method for measuring the thickness of the layer including the covering material 111 is not particularly limited. For example, in XPS measurement, the thickness can be estimated by observing a specific peak caused by the covering material 111 while etching the surface of the covering active material 130 by ion beam etching. Alternatively, the thickness of the layer including the covering material 111 can be measured by direct observation using a transmission electron microscope.

[0099] The covering material 111 may also cover the entire surface of the particle-shaped positive electrode active material 110. If such a structure is used, direct contact between the positive electrode active material 110 and the particles of the solid electrolyte can be suppressed, and the side reaction of the solid electrolyte can be suppressed. Therefore, the charge and discharge efficiency can be improved.

[0100] Alternatively, the covering material 111 may cover only a portion of the surface of the particulate positive electrode active material 110. The particles of the plurality of positive electrode active materials 110 are in direct contact with each other through the portion without the covering material 111, thereby improving the electron conductivity between the particles of the positive electrode active material 110. Therefore, the battery can operate at a high output power.

[0101] The positive electrode active material 110 includes a material having the property of embedding and de-embedding metal ions (e.g., lithium ions). As the positive electrode active material 110, for example, lithium-containing transition metal oxides, transition metal fluorides, polyanion materials, fluorinated polyanion materials, transition metal sulfides, transition metal sulfur oxides, transition metal nitrogen oxides, etc. can be used. In particular, when lithium-containing transition metal oxides are used as the positive electrode active material 110, the manufacturing cost can be reduced and the average discharge voltage can be increased.

[0102] The positive electrode active material 110 may also include a lithium-containing transition metal oxide having a layered rock salt structure. Lithium is easily intercalated and deintercalated in the lithium-containing transition metal oxide having a layered rock salt structure, and the capacity per unit weight is also large. Therefore, by using such a material, excellent charge and discharge characteristics can be achieved.

[0103] Examples of lithium-containing transition metal oxides having a layered rock salt structure include lithium nickel-cobalt-aluminum oxide, lithium nickel-cobalt-manganese oxide, lithium cobalt oxide, etc. The positive electrode active material 110 may include a single active material or a plurality of active materials having different compositions.

[0104] The positive electrode active material 110 may also include at least one selected from the group consisting of nickel-cobalt-lithium aluminum oxide and nickel-cobalt-lithium manganese oxide. The positive electrode active material 110 may be nickel-cobalt-lithium aluminum oxide or nickel-cobalt-lithium manganese oxide. The positive electrode active material 110 may also be, for example, Li(NiCoAl)O2. The positive electrode active material 110 may also be, for example, Li(NiCoMn)O2. If such a structure is used, the energy density and charge and discharge efficiency of the battery can be further improved.

[0105] The electron conductivity of the positive electrode active material 110 can also be 10 at room temperature (25°C). -9 Scm -1 Above, 10 -8 Scm -1 Above, 10 -7 Scm -1 Above, 10 -6 Scm -1 Above, 10 -5 Scm -1 Above, or 10 -4 Scm -1 When the electron conductivity of the positive electrode active material 110 is high, the oxidation reaction of the solid electrolyte in the positive electrode of the battery is easily promoted. In such a case, the technology disclosed in the present invention is more effective.

[0106] The positive electrode active material 110 has a particle shape, for example. The shape of the particles of the positive electrode active material 110 is not particularly limited. The shape of the particles of the positive electrode active material 110 may be spherical, ellipsoidal, scaly, or fibrous.

[0107] The coating active material 130 can be produced by, for example, the method described below.

[0108] First, prepare the positive electrode active material 110. The powder of the positive electrode active material 110 is commercially available.

[0109] Next, the positive electrode active material 110 is covered with a covering material. The covering method is not particularly limited. Examples of the method for covering the positive electrode active material 110 with a covering material include a liquid phase covering method and a gas phase covering method.

[0110] For example, in the liquid phase coating method, a precursor solution of the coating material is applied to the surface of the positive electrode active material 110. For example, in the case of forming a coating material containing lithium niobate, the precursor solution can be a peroxo complex containing niobium ([Nb(O2)4] 3- ) and a complex solution of lithium ions. The complex solution can be obtained, for example, by preparing a transparent solution using hydrogen peroxide, niobic acid and ammonia water and then adding a lithium compound to the transparent solution. Examples of the lithium compound include LiOH, LiNO3, Li2SO4, and the like.

[0111] The method of applying the precursor solution to the surface of the positive electrode active material 110 is not particularly limited. For example, the precursor solution can be applied to the surface of the positive electrode active material 110 using a rotating flow granulation coating device. If a rotating flow granulation coating device is used, the precursor solution can be blown onto the positive electrode active material 110 while the positive electrode active material 110 is rotated and flowed, and the precursor solution is applied to the surface of the positive electrode active material 110. Thus, a precursor film is formed on the surface of the positive electrode active material 110. Next, the precursor film is dried. The formation of the precursor film and the drying of the precursor film can also be performed simultaneously. Thus, a positive electrode active material 110 covered with lithium niobate can be obtained. The drying conditions are, for example, a dry air atmosphere, an atmosphere temperature of 200°C to 300°C, and more than 10 minutes and less than 720 minutes.

[0112] The covering material 111 can also be formed by a so-called sol-gel method. That is, the precursor solution can also be a mixed solution (sol solution) of a solvent, a lithium alkoxide and a niobium alkoxide. As lithium alkoxide, lithium ethoxide can be listed. As niobium alkoxide, niobium ethoxide can be listed. The solvent is, for example, an alcohol such as ethanol. The amount of lithium alkoxide and niobium alkoxide is adjusted according to the target composition of the covering material. Water can also be added to the precursor solution as needed. The precursor solution can be acidic or alkaline.

[0113] As the vapor phase coating method, there can be cited pulsed laser deposition (PLD) method, vacuum evaporation method, sputtering method, thermal chemical vapor deposition (CVD) method, plasma chemical vapor deposition method, etc. For example, in the PLD method, a high-energy pulse laser (for example, KrF excimer laser, wavelength: 248nm) is irradiated on the ion conductive material as a target, so that the sublimated ion conductive material is deposited on the surface of the positive electrode active material 110. In the case of forming a layer containing LiNbO3, LiNbO3 sintered at a high density can be used as a target.

[0114] Next, the positive electrode active material 110 covered with the covering material is subjected to carbonation treatment. Specifically, the positive electrode active material 110 covered with the covering material is brought into contact with (exposed to) a treatment gas containing carbon dioxide gas at a concentration higher than that of the atmosphere. If such a method is used, the concentration of carbon constituting carbonate ions in the surface layer of the positive electrode active material 110 covered with the covering material can be increased.

[0115] The time for the carbonation treatment is, for example, 10 minutes to 720 minutes.

[0116] The carbonation treatment can be carried out at room temperature (20°C ± 15°C) or at a temperature higher than room temperature. That is, in the carbonation treatment, the positive electrode active material 110 covered with the covering material can also be heated while being in contact with the treatment gas. By heating, the concentration of carbon constituting carbonate ions in the surface layer of the positive electrode active material 110 covered with the covering material can be effectively increased. The ambient temperature during heating is, for example, above 50°C and below 300°C, preferably above 100°C and below 300°C. By appropriately adjusting the heating temperature, the concentration of carbon constituting carbonate ions can be appropriately controlled.

[0117] In the carbonation treatment, a treatment gas whose main component is carbon dioxide gas can be used. As a result, the concentration of carbonate ions in the surface layer of the positive electrode active material 110 covered with the covering material can be effectively increased. Typically, pure carbon dioxide gas can be used as the treatment gas. The so-called "main component" refers to the component that contains the most by volume ratio.

[0118] Through the above steps, the covered active material 130 can be obtained.

[0119] (Implementation Method 2)

[0120] Figure 2 1 is a cross-sectional view showing a schematic structure of a positive electrode material 1000 in Embodiment 2. The positive electrode material 1000 is a mixture of the coating active material 130 and the solid electrolyte 100 in Embodiment 1.

[0121] The positive electrode material 1000 includes a coating active material 130 and a solid electrolyte 100. The coating active material 130 and the solid electrolyte 100 are in contact with each other.

[0122] The solid electrolyte 100 may include at least one selected from the group consisting of a sulfide solid electrolyte, a halide solid electrolyte, and an acyl halide solid electrolyte. If such a configuration is used, the ion conductivity of the solid electrolyte 100 can be improved. Thus, the resistance of the battery can be reduced.

[0123] As halide solid electrolytes, Li3YX6, Li2MgX4, Li2FeX4, Li(Al, Ga, In)X4, Li3(Al, Ga, In)X6 and the like can be listed.

[0124] Examples of the acid halide solid electrolyte include Li a (Ta, Nb) b O c X d a, b, c and d are each independently a value greater than 0. X includes at least one selected from the group consisting of F, Cl, Br and I.

[0125] As sulfide solid electrolytes, Li2S-P2S5, Li2S-SiS2, Li2S-B2S3, Li2S-GeS2, Li 3.25 Ge 0.25 P 0.75 S4, Li 10 GeP2S 12 Etc. LiX, Li2O, MO can also be added to them q , Li p MO q etc. Wherein, the element X in "LiX" is at least one selected from the group consisting of F, Cl, Br and I. q " and "Li p MO q The element M in "MO" is at least one selected from the group consisting of P, Si, Ge, B, Al, Ga, In, Fe and Zn. q " and "Li p MO q " where p and q are independent natural numbers.

[0126] The solid electrolyte 100 may include two or more materials selected from the above materials. For example, the solid electrolyte 100 may include a halide solid electrolyte and a sulfide solid electrolyte.

[0127] In the present disclosure, when an element in a formula is expressed as "(Al, Ga, In)", the description indicates at least one element selected from the element group in the parentheses. That is, "(Al, Ga, In)" has the same meaning as "at least one selected from the group consisting of Al, Ga and In". The same applies to other elements.

[0128] The shape of the solid electrolyte 100 is not particularly limited, and may be, for example, a needle shape, a spherical shape, an ellipsoidal spherical shape, etc. For example, the solid electrolyte 100 may be in a particle shape.

[0129] For example, when the solid electrolyte 100 is in the shape of particles (e.g., spheres), the median particle size may be 100 μm or less. When the median particle size of the solid electrolyte 100 is 100 μm or less, the covering active material 130 and the solid electrolyte 100 can form a good dispersion state in the positive electrode material 1000. As a result, the charge and discharge characteristics of the battery are improved. In Embodiment 1, the median particle size of the solid electrolyte 100 may also be 10 μm or less.

[0130] According to the above configuration, in the positive electrode material 1000 , the covering active material 130 and the solid electrolyte 100 can be in a well-dispersed state.

[0131] The median particle size of the solid electrolyte 100 may be smaller than the median particle size of the covering active material 130 .

[0132] According to the above configuration, the solid electrolyte 100 and the coating active material 130 can be in a better dispersed state in the positive electrode material 1000 .

[0133] The median particle size of the coating active material 130 may be greater than or equal to 0.1 μm and less than or equal to 100 μm.

[0134] When the median particle size of the coating active material 130 is 0.1 μm or more, the coating active material 130 and the solid electrolyte 100 can be well dispersed in the positive electrode material 1000. As a result, the charge and discharge characteristics of the battery are improved.

[0135] When the median particle size of the coating active material 130 is 100 μm or less, the diffusion rate of lithium in the coating active material 130 can be sufficiently ensured. Therefore, the battery can operate at a high output.

[0136] The median particle size of the coating active material 130 may be larger than the median particle size of the solid electrolyte 100. Thus, the coating active material 130 and the solid electrolyte 100 can be in a well-dispersed state.

[0137] In the positive electrode material 1000, the particles of the solid electrolyte 100 and the particles covering the active material 130 may also be Figure 2 The solid electrolyte 100 may fill the gaps between the particles of the covering active material 130. In this case, the covering material 111 and the solid electrolyte 100 are in contact with each other.

[0138] The positive electrode material 1000 may include a plurality of particles of the solid electrolyte 100 and a plurality of particles covering the active material 130 .

[0139] The content of the solid electrolyte 100 in the positive electrode material 1000 and the content of the covering active material 130 may be the same as or different from each other.

[0140] In this specification, the “median diameter” refers to the particle diameter at which the cumulative volume in the volume-based particle size distribution is 50%. The volume-based particle size distribution is measured, for example, by a laser diffraction measuring device or an image analyzer.

[0141] (Implementation 3)

[0142] Embodiment 3 will be described below. The description overlapping with that of Embodiment 1 described above will be appropriately omitted.

[0143] Figure 3 This is a cross-sectional view schematically showing the structure of a battery 2000 in the third embodiment.

[0144] The battery 2000 includes a positive electrode 201 , an electrolyte layer 202 , and a negative electrode 203 .

[0145] The positive electrode 201 includes the positive electrode material 1000 in Embodiment 1. The benefits described in Embodiment 1 can be obtained in the positive electrode 201 .

[0146] The electrolyte layer 202 is disposed between the positive electrode 201 and the negative electrode 203 .

[0147] By utilizing the above configuration, the charge and discharge efficiency of the battery 2000 can be improved.

[0148] The thickness of the positive electrode 201 may be 10 μm or more and 500 μm or less. When the thickness of the positive electrode 201 is 10 μm or more, the energy density of the battery 2000 can be sufficiently ensured. When the thickness of the positive electrode 201 is 500 μm or less, the battery 2000 can operate at a high output.

[0149] The electrolyte layer 202 is a layer containing an electrolyte. The electrolyte is, for example, a solid electrolyte. That is, the electrolyte layer 202 may also be a solid electrolyte layer. Hereinafter, the solid electrolyte 100 contained in the positive electrode material 1000 is sometimes referred to as the "first solid electrolyte", and the solid electrolyte contained in the electrolyte layer 202 is sometimes referred to as the "second solid electrolyte".

[0150] As the second solid electrolyte, the material exemplified in Embodiment 2 may be used. That is, the electrolyte layer 202 may include a solid electrolyte having the same composition as that of the solid electrolyte 100 included in the positive electrode material 1000. The electrolyte layer 202 may include, for example, a sulfide solid electrolyte.

[0151] By utilizing the above configuration, the charge and discharge efficiency of the battery 2000 can be further improved.

[0152] Alternatively, the electrolyte layer 202 may include a solid electrolyte having a composition different from that of the solid electrolyte 100 included in the positive electrode material 1000. For example, the electrolyte layer 202 may include a sulfide solid electrolyte having a composition different from that of the solid electrolyte 100.

[0153] By utilizing the above configuration, the output power density and the charge and discharge efficiency of the battery 2000 can be improved.

[0154] The electrolyte layer 202 may include at least one selected from the group consisting of a halide solid electrolyte, an acyl halide solid electrolyte, an oxide solid electrolyte, a polymer solid electrolyte, and a complex hydride solid electrolyte. As the halide solid electrolyte and the acyl halide solid electrolyte, the materials exemplified in Embodiment 2 can be used.

[0155] As oxide solid electrolytes, for example, NASICON solid electrolytes represented by LiTi2(PO4)3 and its element substitution products, (LaLi)TiO3-based perovskite solid electrolytes, and Li 14 ZnGe4O 16 , LISICON type solid electrolyte represented by Li4SiO4, LiGeO4 and their element substitution bodies, Li7La3Zr2O 12 Garnet-type solid electrolytes represented by Li3N and its H-substituted bodies, Li3PO4 and its N-substituted bodies, glass or glass ceramics obtained by adding Li2SO4, Li2CO3 and other materials to a base material containing Li-BO compounds such as LiBO2 and Li3BO3, etc.

[0156] As a polymer solid electrolyte, for example, a compound of a polymer compound and a lithium salt can be used. The polymer compound may also have an ethylene oxide structure. By having an ethylene oxide structure, the polymer compound can contain a large amount of lithium salt, thereby further improving the ion conductivity. As lithium salts, LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, etc. can be used. As a lithium salt, one lithium salt selected from them may be used alone, or a mixture of two or more lithium salts selected from them may be used.

[0157] As the complex hydride solid electrolyte, for example, LiBH4-LiI, LiBH4-P2S5, etc. can be used.

[0158] The electrolyte layer 202 may contain the second solid electrolyte as a main component. That is, the electrolyte layer 202 may contain 50% or more (ie, 50% by mass or more) of the second solid electrolyte in terms of mass ratio relative to the total mass of the electrolyte layer 202 .

[0159] By utilizing the above configuration, the charge and discharge characteristics of the battery 2000 can be further improved.

[0160] The electrolyte layer 202 may contain 70% or more (ie, 70% by mass or more) of the second solid electrolyte in terms of a mass ratio relative to the total mass of the electrolyte layer 202 .

[0161] By utilizing the above configuration, the charge and discharge characteristics of the battery 2000 can be further improved.

[0162] The electrolyte layer 202 may contain the second solid electrolyte as a main component, and may further contain inevitable impurities, or starting materials, by-products, and decomposition products used when synthesizing the second solid electrolyte.

[0163] The electrolyte layer 202 may contain 100% (ie, 100% by mass) of the second solid electrolyte in terms of a mass ratio relative to the total mass of the electrolyte layer 202 excluding inevitable impurities.

[0164] By utilizing the above configuration, the charge and discharge characteristics of the battery 2000 can be further improved.

[0165] As described above, the electrolyte layer 202 may be composed only of the second solid electrolyte.

[0166] The electrolyte layer 202 may include only one solid electrolyte selected from the above-mentioned group of solid electrolytes, or may include two or more solid electrolytes selected from the above-mentioned group of solid electrolytes. The plurality of solid electrolytes have different compositions from each other. For example, the electrolyte layer 202 may also include a halide solid electrolyte and a sulfide solid electrolyte.

[0167] The thickness of the electrolyte layer 202 may be 1 μm or more and 300 μm or less. When the thickness of the electrolyte layer 202 is 1 μm or more, the positive electrode 201 and the negative electrode 203 can be separated more reliably. When the thickness of the electrolyte layer 202 is 300 μm or less, operation with high output power can be achieved.

[0168] The negative electrode 203 includes a material having the property of inserting and removing metal ions (for example, lithium ions). The negative electrode 203 includes, for example, a negative electrode active material.

[0169] For the negative electrode active material, metal materials, carbon materials, oxides, nitrides, tin compounds, silicon compounds, etc. can be used. The metal material can also be a single metal. Alternatively, the metal material can also be an alloy. Examples of metal materials include lithium metal and lithium alloys. Examples of carbon materials include natural graphite, coke, carbon in the process of graphitization, carbon fiber, spherical carbon, artificial graphite, amorphous carbon, etc. From the viewpoint of capacity density, silicon (Si), tin (Sn), silicon compounds or tin compounds can be used.

[0170] The negative electrode 203 may include a solid electrolyte (third solid electrolyte). With such a configuration, the lithium ion conductivity inside the negative electrode 203 can be improved, and the negative electrode 203 can be operated at a high output. As the solid electrolyte, the above-mentioned materials can also be used.

[0171] The median particle size of the particles of the negative electrode active material can also be greater than 0.1 μm and less than 100 μm. When the median particle size of the particles of the negative electrode active material is greater than 0.1 μm, in the negative electrode 203, the particles of the negative electrode active material and the solid electrolyte can form a good dispersion state. As a result, the charge and discharge characteristics of the battery 2000 are improved. In addition, when the median particle size of the particles of the negative electrode active material is less than 100 μm, the lithium diffusion in the particles of the negative electrode active material becomes faster. Therefore, the battery 2000 can operate at a high output power.

[0172] The median diameter of the particles of the negative electrode active material may be larger than the median diameter of the particles of the solid electrolyte contained in the negative electrode 203. This allows the negative electrode active material and the solid electrolyte to be well dispersed.

[0173] When the volume ratio of the negative electrode active material to the solid electrolyte in the negative electrode 203 is expressed as "v2:100-v2", the volume ratio v2 of the negative electrode active material may also satisfy 30≤v2≤95. When 30≤v2 is satisfied, the energy density of the battery 2000 can be sufficiently ensured. In addition, when v2≤95 is satisfied, it is possible to operate at a high output power.

[0174] The thickness of the negative electrode 203 may be 10 μm or more and 500 μm or less. When the thickness of the negative electrode 203 is 10 μm or more, the energy density of the battery 2000 can be sufficiently ensured. When the thickness of the negative electrode 203 is 500 μm or less, the battery 2000 can operate at a high output.

[0175] In at least one of the positive electrode 201, the electrolyte layer 202 and the negative electrode 203, a binder may also be included for the purpose of improving the adhesion of the particles. The binder is used to improve the adhesion of the material constituting the electrode. As a binder, polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, aramid resin, polyamide, polyimide, polyamide-imide, polyacrylonitrile, polyacrylic acid, polymethyl acrylate, polyethyl acrylate, polyhexyl acrylate, polymethacrylic acid, polymethyl methacrylate, polyethyl methacrylate, polyhexyl methacrylate, polyvinyl acetate, polyvinyl pyrrolidone, polyether, polyether sulfone, hexafluoropolypropylene, styrene butadiene rubber, carboxymethyl cellulose, etc. can be listed. In addition, as a binder, a copolymer of two or more materials selected from tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkyl vinyl ether, vinylidene fluoride, chlorotrifluoroethylene, ethylene, propylene, pentafluoropropylene, fluoromethyl vinyl ether, acrylic acid, hexadiene can be used. Furthermore, two or more selected from these may be mixed and used as a binder.

[0176] At least one of the positive electrode 201 and the negative electrode 203 may also include a conductive auxiliary agent for the purpose of improving electronic conductivity. As the conductive auxiliary agent, for example, graphite such as natural graphite or artificial graphite, carbon black such as acetylene black and Ketjen black, conductive fibers such as carbon fibers or metal fibers, metal powders such as carbon fluoride and aluminum, conductive whiskers such as zinc oxide or potassium titanate, conductive metal oxides such as titanium oxide, polyaniline, polypyrrole, and conductive polymer compounds such as polythiophene can be used. When a carbon conductive auxiliary agent is used, low cost can be achieved.

[0177] The battery 2000 in the third embodiment can be configured as a battery in various shapes such as a coin-shaped, cylindrical, square, sheet-shaped, button-shaped, flat, and laminated type.

[0178] Example

[0179] Hereinafter, the details of the present disclosure will be described using Examples and Comparative Examples.

[0180] 《Example 1》

[0181] [Production of active material covering]

[0182] (Preparation of complex solution)

[0183] 870 g of 30% by mass hydrogen peroxide was added to a container, and 987 g of ion exchange water and 177 g of niobic acid (Nb2O5·3H2O (Nb2O5 water content 72%)) were added. Next, 87.9 g of 28% by mass ammonia water was added to the container. Next, the contents in the container were stirred thoroughly to obtain a transparent solution. Next, 40 g of lithium hydroxide·monohydrate (LiOH·H2O) was added to the transparent solution to obtain a complex solution containing a peroxo complex of niobium and lithium ions. The molar concentrations of Li and Nb in the complex solution were both 0.47 mol / kg.

[0184] (Spraying and drying of complex solution)

[0185] The complex solution was sprayed on the positive electrode active material using a rotary flow coating device (MP-01 manufactured by Powrex Corporation), and the complex solution was dried simultaneously with the spraying, thereby forming a layer containing a precursor of lithium niobate on the surface of the particles of the positive electrode active material. The amount of the complex solution used was 720 g. As the positive electrode active material, LiNi 0.8 Co 0.15 Al 0.05 O2 (NCA, average particle size 5 μm). The amount of positive electrode active material used was 2000 g. The operating conditions of the rotary flow coating device were as follows.

[0186] Inhalation gas: Nitrogen

[0187] Intake temperature: 200℃

[0188] Air intake volume: 0.4m 3 / min

[0189] Rotor speed: 400 rpm

[0190] Spray speed: 10g / min

[0191] (Heat Treatment)

[0192] The positive electrode active material covered with the precursor of lithium niobate was heat treated using a muffle furnace. The heat treatment conditions were 220°C and 4 hours. As a result, a covered active material having a positive electrode active material and lithium niobate attached to its surface was obtained. That is, the covering material in Example 1 was lithium niobate (LiNbO3).

[0193] (Carbonation treatment)

[0194] After the coated active material was placed in a tubular electric furnace, carbon dioxide gas (CO2 gas) was flowed at a flow rate of 1 L / min and allowed to stand for 1 hour to allow the carbon dioxide gas to contact the coated active material. Thus, a powdered coated active material of Example 1 was obtained. The purity of the carbon dioxide gas was 99.999%.

[0195] [XPS measurement of covering active substances]

[0196] The XPS measurement of the coated active material in Example 1 was performed under the following conditions. For the XPS measurement, Quantera SXM (manufactured by ULVAC-PHI) was used.

[0197] X-ray source: Al monochromatic (25W, 15kV)

[0198] Electron / ion neutralization gun: ON

[0199] Photoelectron extraction angle: 45 degrees

[0200] Carbon (C) was selected as the element to be measured, and the scanning range of the bonding energy was set to 275 eV to 295 eV (C1s orbital). The peaks of the XPS spectrum in the range of 275 eV to 295 eV were separated, and the area of ​​each peak was calculated. Specifically, the spectrum was separated into peaks attributable to CC bonds and peaks attributable to OC=O bonds, and the area of ​​each peak (integrated peak area) was calculated. That is, the ratio r of the area of ​​the peak attributable to the OC=O bond to the total area of ​​the C1s peak was calculated. C1 Using X C =X Ctot × C1 , calculate the atomic ratio X of carbon constituting carbonate ions C The ratio of OC=O bonds is calculated by comparing the atomic ratio of carbon to all elements (Li, C, O, Al, Co, Ni, Nb) Ctot Multiply to determine the composition of CO3 2- The atomic ratio of carbon is X C In the analysis of XPS spectra, peak fitting is performed using a pseudo-Voigt function. Since the peak position of each bond is not uniformly determined due to the influence of charge, the relative positions and intensity ratios of the multiple peaks of each component are fixed for fitting.

[0201] Niobium (Nb) was selected as the element to be measured, and the scanning range of the bonding energy was set to 200 eV to 212 eV (Nb 3d orbital). The atomic ratio X of Nb was calculated using the Nb 3d peak. Nb .

[0202] The atomic ratio of carbon constituting carbonate ions is XC Atomic ratio X relative to Nb Nb The atomic ratio of carbon to carbonate ions is X C The total ratio of X C / (X Nb +X C ) is 0.29.

[0203] [Preparation of sulfide solid electrolyte]

[0204] In an argon glove box with an Ar atmosphere at a dew point below -60°C, Li2S and P2S5 are weighed in a molar ratio of Li2S:P2S5=75:25. They are crushed and mixed in a mortar to obtain a mixture. Thereafter, the mixture is ground using a planetary ball mill (manufactured by FRITSCH, model P-7) at 510 rpm for 10 hours. Thus, a glassy solid electrolyte is obtained. The glassy solid electrolyte is heat treated in an inert atmosphere at 270 degrees for 2 hours. Thus, a glass-ceramic solid electrolyte, namely Li2S-P2S5, is obtained.

[0205] [Battery production]

[0206] (Production of positive electrode)

[0207] The covered active material and the sulfide solid electrolyte of Example 1 are weighed in a volume ratio of (covered active material): (sulfide solid electrolyte) = 7:3. They are added to a tetrahydroxynaphthalene solvent together with vapor grown carbon fiber (VGCF) as a conductive aid and styrene-ethylene-butylene-styrene block copolymer (SEBS) as a binder. The resulting mixture is fully dispersed with an ultrasonic homogenizer to prepare a positive electrode paste. The amount of the conductive aid is 2 parts by mass relative to 100 parts by mass of the covered active material. The amount of the binder is 0.4 parts by mass relative to 100 parts by mass of the covered active material. "VGCF" is a registered trademark of Resonac Corporation.

[0208] (Production of negative electrode)

[0209] Lithium titanate and sulfide solid electrolyte as negative electrode active materials are weighed in a volume ratio of (lithium titanate): (sulfide solid electrolyte) = 6.5:3.5. They are added to a tetrahydroxynaphthalene solvent together with vapor-grown carbon fiber (VGCF) as a conductive aid and styrene-ethylene-butylene-styrene block copolymer (SEBS) as a binder. The resulting mixture is fully dispersed with an ultrasonic homogenizer to prepare a negative electrode paste. The amount of the conductive aid is 1 part by mass relative to 100 parts by mass of the negative electrode active material. The amount of the binder is 2 parts by mass relative to 100 parts by mass of the negative electrode active material.

[0210] (Fabrication of all-solid-state batteries)

[0211] The positive electrode paste was applied to an aluminum foil as a positive electrode current collector by a doctor blade method using an applicator to form a coating film, and the coating film was dried on a hot plate at 100° C. for 30 minutes. Thus, a positive electrode having a positive electrode current collector and a positive electrode active material layer was obtained.

[0212] Next, the positive electrode is pressed. The surface of the pressed positive electrode active material layer is coated with an electrolyte layer forming paste containing a sulfide solid electrolyte by a die coater to obtain a laminate of the positive electrode and the coating film. The laminate is dried on a hot plate at 100°C for 30 minutes. Thereafter, the laminate is rolled at a linear pressure of 2 ton / cm. Thus, a positive electrode side laminate having a positive electrode collector, a positive electrode active material layer and a solid electrolyte layer is obtained.

[0213] The negative electrode paste was applied on a nickel foil as a negative electrode current collector to form a coating film, and the coating film was dried on a hot plate at 100° C. for 30 minutes. Thus, a negative electrode having a negative electrode current collector and a negative electrode active material layer was obtained.

[0214] Next, the negative electrode is pressed. The electrolyte layer forming paste is applied to the surface of the pressed negative electrode active material layer using a die coater to obtain a laminate of the negative electrode and the coating film. The laminate is dried on a hot plate at 100°C for 30 minutes. Thereafter, the laminate is rolled at a linear pressure of 2 ton / cm. Thus, a negative electrode side laminate having a negative electrode collector, a negative electrode active material layer and a solid electrolyte layer is obtained.

[0215] The positive electrode side laminate and the negative electrode side laminate are punched out separately and arranged into a specified shape. The positive electrode side laminate and the negative electrode side laminate are overlapped in such a way that the solid electrolyte layers are in contact with each other. Afterwards, the positive electrode side laminate and the negative electrode side laminate are rolled at 130°C and a linear pressure of 2 ton / cm. Thus, a power generation element having a positive electrode, a solid electrolyte layer and a negative electrode in sequence is obtained. The positive terminal and the negative terminal are installed on the obtained power generation element, sealed in a container made of a laminated film, and constrained at a pressure of 5 MPa, thereby obtaining the all-solid-state battery of Example 1.

[0216] [DC resistance measurement]

[0217] The DC resistance of the all-solid-state battery was measured by the following method: constant current charging was performed at a current of 1C, and after the battery voltage reached 2.95V, constant voltage charging was performed at 2.95V, and charging was terminated when the charging current reached 0.01C. Then, constant current discharge was performed at a current of 1C, and discharge was terminated when the battery voltage dropped to 1.5V.

[0218] To measure the DC resistance, the all-solid-state battery was charged again to 2.2 V at a current of C / 3 and then discharged at a current of 4C. The DC resistance was calculated by dividing the difference between the open circuit voltage immediately before the 4C discharge and the voltage at the moment 10 seconds after the discharge start by the 4C current value. The calculated DC resistance was regarded as the "initial resistance" before the endurance test. The results are shown in Table 1 and Figure 4 middle.

[0219] In Table 1 and Figure 4 In the figure, the initial resistance is a relative value when the initial resistance of Comparative Example 1 is regarded as "100". Figure 4 It means X C / (X Nb +X C ) and the relationship between the initial resistance and X C / (X Nb +X C ) and the resistance change rate. The horizontal axis represents X C / (X Nb +X C The vertical axis represents the ratio of the initial resistance and the resistance change rate relative to Comparative Example 1.

[0220] [Durability test]

[0221] The all-solid-state battery is placed in a thermostatic chamber at 60°C, and a charge and discharge cycle test is performed to evaluate the electrochemical durability of the all-solid-state battery. First, a constant current charge is performed at a current of 5C until the upper limit voltage reaches 2.7V, and then a constant voltage charge is performed until the current decays to 1 / 3. Next, a constant current discharge is performed at a current of 1C until the lower limit voltage is 1.8V. This series of charge and discharge is repeated for 90 cycles as a durability test. The small increase in resistance caused by the durability test means that the battery has excellent cycle characteristics.

[0222] After the endurance test, the DC resistance was measured by the method described above, and the DC resistance after the endurance test was calculated. The resistance change rate caused by the endurance test was calculated based on the following formula (6). The results are shown in Table 1 and Figure 4 In Table 1 and Figure 4 In FIG. 1 , the resistance change rate is a relative value when the resistance change rate of Comparative Example 1 is regarded as “100”.

[0223] (Resistance change rate) = 100 × {(DC resistance after endurance test) / (initial resistance)} / {(DC resistance after endurance test of Comparative Example 1) / (initial resistance of Comparative Example 1)} (6)

[0224] 《Example 2》

[0225] A coated active material of Example 2 was prepared by the same method as in Example 1 except that the carbonation treatment was performed under the following conditions.

[0226] (Carbonation treatment)

[0227] After the coated active material was placed in the tubular electric furnace, the temperature inside the tubular electric furnace was raised to 100° C. at a rate of 5 K / min while carbon dioxide gas was circulated at a flow rate of 1 L / min, and maintained at 100° C. for 1 hour. Thereafter, the coated active material was slowly cooled until the inside of the tubular electric furnace dropped to room temperature. Thus, the powdered coated active material of Example 2 was obtained.

[0228] 《Examples 3 to 6》

[0229] The coated active material was prepared by the same method as in Example 2 except that the carbonation treatment was carried out under the following conditions. The C1s XPS spectrum of the coated active material of Example 6 is shown in Figure 7 middle.

[0230] (Carbonation treatment)

[0231] After the covered active material is arranged in the tubular electric furnace, the temperature inside the tubular electric furnace is raised to a specified temperature at a rate of 10K / min while the carbon dioxide gas is circulated at a flow rate of 1L / min, and maintained at the specified temperature for 1 hour. Thereafter, it is cooled until it reaches near room temperature. Thus, the powdered covered active materials of Examples 3 to 6 are obtained. The specified temperature in Example 3 is 150°C. The specified temperature in Example 4 is 250°C. The specified temperature in Example 5 is 300°C.

[0232] The prescribed temperature in Example 6 is 350°C.

[0233] Comparative Example 1

[0234] The coated active material of Comparative Example 1 was prepared by the same method as Example 1 except that the carbonic acid treatment was omitted. The C1s XPS spectrum of the coated active material of Comparative Example 1 is shown in FIG. Figure 7 middle.

[0235] For the coated active materials of Examples 2 to 6 and Comparative Example 1, the ratio X C / (X Nb +X C ), initial resistance and resistance change rate are shown in Table 1.

[0236] Table 1

[0237]

[0238] ※The initial resistance and resistance change rate are relative values ​​when the values ​​of Comparative Example 1 are regarded as "100".

[0239] [Investigation]

[0240] In Comparative Example 1, C / (X Nb +X C ) is 0.28. As shown in the results of Examples 1 to 6, by performing carbonation treatment at room temperature or at a temperature higher than room temperature, the ratio X C / (X Nb +X C ) value increases. That is, the atomic ratio of carbon constituting carbonate ions increases. According to Examples 1 to 5, by performing carbonic acid treatment, not only the resistance change rate is improved, but also the initial resistance of the battery is reduced. The reason for obtaining such an effect is speculated as follows. When synthesizing the positive electrode active material, no lithium that contributes to the reaction remains in the form of Li2O on the surface of the particles of the positive electrode active material. Lithium compounds such as Li2O absorb moisture and / or carbon dioxide in the air to generate compounds such as LiOH and LiHCO3. These compounds are electrochemically unstable and active. On the other hand, by performing carbonic acid treatment, these compounds are changed to Li2CO3 and stabilized. It is believed that as a result, the side reactions inside the battery can be suppressed and the initial resistance of the battery is reduced.

[0241] The effect of reducing the initial resistance and the resistance change rate becomes the greatest at 250°C. C / (X Nb +X C ) is 0.45. C / (X Nb +X C ) exceeds 0.45, then initial resistance and resistance change rate show increasing tendency.As its reason, it is thought that the increase of the thickness of the layer (carbonic acid layer) of the carbon that comprises carbonate ion hinders ion conduction.In embodiment 6, although resistance change rate reduces, initial resistance increases compared with comparative example 1.

[0242] [Evaluation of Thickness of Layer Containing Carbon Constituting Carbonate Ions (Carbonate Layer)]

[0243] The active material covered in Comparative Example 1 and Example 4 was argon etched to remove the elements on the surface. XPS measurement was performed at each preset etching time to obtain a distribution diagram of element concentration. The relationship between etching time and etching depth was obtained by etching a SiO2 film with a known thickness. Using the relationship between etching time and etching depth, the SiO2 conversion thickness was calculated from the etching time. The results are shown in Figure 5 and Figure 6 middle.

[0244] Figure 5 This is a graph showing the element distribution in the depth direction of the covering active material of Comparative Example 1. The detected elements are carbon and niobium. The horizontal axis represents the depth from the surface. The vertical axis represents the atomic ratio of carbon and niobium to all elements. In Comparative Example 1, the concentration of niobium is approximately constant from the surface to 30nm. The concentration of niobium gradually decreases in the area deeper than 30nm. It is believed that LiNbO3 exists from the surface to about 30nm, and the defective part of the layer of the covering material is generated by etching deeper than 30nm, and the signal is reduced.

[0245] Figure 6 It is a chart showing the element distribution diagram in the depth direction of the covering active material of Example 4. Near the surface, the concentration of niobium is low and the concentration of carbon is high. That is, a layer of carbon containing carbonate ions is formed on the surface of the covering active material. The ratio of carbon decreases sharply from the surface to a depth of 20nm. After that, the ratio of carbon decreases slowly. Since the ratio of niobium reaches a maximum at 20nm, it is believed that the thickness of the carbonate layer is at least about 20nm in terms of SiO2 conversion. The ratio of carbon is constant after 50nm. Therefore, it is believed that the thickness of the carbonate layer is about 50nm at most. It is believed that the thickness of the carbonate layer increases with the increase of the treatment temperature in the carbonation treatment and increases with the increase of the treatment time in the carbonation treatment.

[0246] When etching a powder sample, the carbon present in the plane perpendicular to the etching beam disappears relatively quickly. The carbon present in the plane parallel to the etching beam is not easy to disappear. Figure 5 ), if etching progresses to a certain extent, the carbon signal disappears. This indicates that the amount of carbon on the surface is very small. In contrast, in Example 4 ( Figure 6 ) even if etching progresses, the carbon signal does not disappear and concentrates at a certain value.

[0247] Industrial Applicability

[0248] The battery disclosed herein can be used as, for example, an all-solid secondary battery.

Claims

1. A covering active material, the covering active material comprising: Positive electrode active material, and a covering material covering at least a portion of the surface of the positive electrode active material, The covering material includes a compound represented by the following composition formula (1) and carbon belonging to a C1s peak having a bonding energy of 288.5±1.5 eV, In formula (1), a, b and c are positive real numbers, M is at least one element other than Li and O, On the surface of the active material, the atomic ratio of carbon is X C The atomic ratio of M to X M Satisfying the following relationship (2): Li a M b O c (1) 0.29≤X C / (X M +X C ) (2)。 2. The covered active material according to claim 1, wherein The atomic ratio X C With the atomic ratio X M Satisfying the following relationship (3): 0.29≤X C / (X M +X C )<0.67 (3)。 3. The covered active material according to claim 1, wherein: The carbon is distributed in a region from the surface covering the active material to a depth of 50 nm or less.

4. The covered active material according to claim 1, wherein The M is at least one element selected from the group consisting of metal elements and semi-metal elements.

5. The covered active material according to claim 1, wherein The M is in a trivalent state, a tetravalent state, a pentavalent state, or a mixed state thereof.

6. The covered active material according to claim 1, wherein The M includes niobium.

7. The covered active material according to claim 1, wherein: The M includes at least one selected from the group consisting of nitrogen, sulfur, and phosphorus.

8. The covered active material according to claim 1, wherein: The positive electrode active material includes a lithium-containing transition metal oxide having a layered rock salt structure. 9 . A battery comprising a positive electrode comprising the covered active material according to claim 1 .

10. A battery comprising: A positive electrode comprising the active material covered according to any one of claims 1 to 8, Negative electrode, and An electrolyte layer is disposed between the positive electrode and the negative electrode.

11. The battery according to claim 10, wherein The electrolyte layer includes a sulfide solid electrolyte.

12. A method for manufacturing a coating of an active substance, comprising: The positive electrode active material is covered with a covering material, and The positive electrode active material covered with the covering material is brought into contact with a processing gas containing carbon dioxide gas at a higher concentration than that of the atmosphere. 13 . The method for producing a covered active material according to claim 12 , further comprising heating the positive electrode active material covered with the covering material while bringing it into contact with the processing gas.

14. The method for producing a coated active material according to claim 12, wherein: The main component of the process gas is the carbon dioxide gas.

Citation Information

Patent Citations

  • Composite active material, all-solid-state battery, and method for producing composite active material

    WO2013099878A1

  • Covered cathode active material and lithium battery

    WO2015050031A1